Pengembangan Sistem Informasi Manajemen Pemesanan Homestay Desa Bajulmati berbasis Website - Adi Setyo Nugroho; Nurudin Santoso; Arief Andy Soebroto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Tourism is the drivers of the economy in various countries in the world. In Indonesia, there are several cities or regions that have developed the potential of tourist areas such as Malang. In 2016, the number of domestic tourists visiting Malang reached 5 million visits, an increase than the previous year which is just 3 million visits. One of the facilities needed by tourists when traveling is lodging at affordable prices such as homestay. Therefore, we need a means of information that can be used by the homestay manager to provide information that is relatively fast for tourists. The porpose of this research is develop an information system for booking homestays in South Malang, especially the Bajulmati village. This research is using Rapid Application Development (RAD) method for system development. Based on the results of the requirements analysis, there were 1 non-functional system requirements and 32 functional requirement. System design and implementation is the next step. System implementation is using the CodeIgniter framework. There several of tests performed, namely compatibility test, integration, unit, and validaton. From validation testing, integration, and unit shows 100% valid. Compatibility testing shown that system can be run in 9 from 12 kind of browser without any functionality problem. Meanwhile, the other browser like internet explorer and safari had a problem in CSS tag that can't be shown.